An additional new species of Peltoperlopsis Illies, 1966 (Plecoptera: Peltoperlidae) from China - Cao, Jinjun; Mo, Raorao; Li, Weihai; Murányi, Dávid (Zootaxa, 2019)
The holotype male of Peltoperlopsis sagittata sp. n. is described from Yunnan Province of southwestern China. The new species represents the third taxon of this peltoperlid genus known from China.